(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Cancer is a disorder which is caused by the uncontrollable multiplication of abnormal cells in the part of the body. Cancer cells have the ability to extend to the other portion of the body in a very fast manner with a short span of time. One of the most dreadful types of cancer is breast cancer. As it name conveys, it is the cancer where the abnormal cells originates in the breast and continues to accumulate, forming a mass of cell. In earlier the breast cancer are detected by mammogram. Machine learning is a usage of artificial intelligence which provides system the capacity to study and develop automatically from experience without being explicitly programmed. The usages of machine learning are in the area like diagnosis, image processing, and classification of data, predication, and regression learning association. In this proposed system the machine learning concepts SVM and NN (Neural Network)are applied for the detection of canceron breast. Compared with SVM classifier NN produces more accurate result.